Inhibition of glycogen synthase kinase 3 by lithium, a mechanism in search of specificity - Chatterjee, Dipashree; Beaulieu, Jean Martin (Frontiers in Molecular Neuroscience, 2022)
Inhibition of Glycogen synthase kinase 3 (GSK3) is a popular explanation for the effects of lithium ions on mood regulation in bipolar disorder and other mental illnesses, including major depression, cyclothymia, and schizophrenia. Contribution of GSK3 is supported by evidence obtained from animal and patient derived model systems. However, the two GSK3 enzymes, GSK3α and GSK3β, have more than 100 validated substrates. They are thus central hubs for major biological functions, such as dopamine-glutamate neurotransmission, synaptic plasticity (Hebbian and homeostatic), inflammation, circadian regulation, protein synthesis, metabolism, inflammation, and mitochondrial functions. The intricate contributions of GSK3 to several biological processes make it difficult to identify specific mechanisms of mood stabilization for therapeutic development. Identification of GSK3 substrates involved in lithium therapeutic action is thus critical. We provide an overview of GSK3 biological functions and substrates for which there is evidence for a contribution to lithium effects. A particular focus is given to four of these: the transcription factor cAMP response element-binding protein (CREB), the RNA-binding protein FXR1, kinesin subunits, and the cytoskeletal regulator CRMP2. An overview of how co-regulation of these substrates may result in shared outcomes is also presented. Better understanding of how inhibition of GSK3 contributes to the therapeutic effects of lithium should allow for identification of more specific targets for future drug development. It may also provide a framework for the understanding of how lithium effects overlap with those of other drugs such as ketamine and antipsychotics, which also inhibit brain GSK3.